POSSIBILITIES OF APPLICATION OF DIGITAL TECHNOLOGIES IN THE ECONOMY OF UZBEKISTAN AS AN EXAMPLE OF COMMERCIAL BANKS - Kuldashev Farid G‘ulom o‘g‘li.; Radjabov Sherzod Umurzakovich (American Journals Publishing, 2023)
In this article, the innovative technologies of the digital economy in the Republic of Uzbekistan and their characteristics, efficiency in use, including the prospects and analytical indicators of the use of innovative technologies in the banking system, are highlighted, and appropriate proposals and recommendations are formulated for the further improvement of remote services of commercial banks.
Keywords: digital economy, blockchain, e-government, crypto-asset, banking, e-payment, e-wallet.